#ConsentObtained – Patient Privacy in the Age of Social Media. Issue 11 (23rd September 2020) - Kumar, Anika; Chen, Nancy; Singh, Amit
Abstract : "I have a rare dermatologic disorder. In medical school, I read a case report about treatment for my disorder. I was surprised to read my history and shocked to see my childhood face staring back at me in the figures section. The case report was written when I was a child and my parents had signed a consent form that stated my case and images could be used for 'educational purposes.' My parents were not notified that my images and case were published. While surprised and shocked to read my history and see images of myself in a medical journal, I trusted my privacy was protected because the journal would only be read by medical professionals. Fast‐forward to today, I do not know how comfortable I would feel if my images were shared on social media, with the potential to reach viewers outside of the medical community. If I were a parent, I would feel even more uncomfortable with reading my child's case on social media, let alone viewing an image of my child." —A.K. Abstract :